Drinking Water Suitability from the Karaga Dam in the Northern Region, Ghana - Amantoge, Achengo Timothy (2014)
A Thesis Submitted to the Department of Theoretical and Applied Biology, College Of Science, Kwame Nkrumah University Of Science and Technology in Partial Fulfillment of the Requirements for the Award of Master of Science Degree in Environmental Science.